Radiation effects on MHD flow past an impulsively started infinite vertical plate with mass diffusion - Chandrakala, P.; Narayana Bhaskar, P. (Zielona Góra: Uniwersytet Zielonogórski)
The effects of thermal radiation on a flow past an impulsively started infinite vertical plate in the presence of a magnetic field have been studied. The fluid considered is a gray, absorbing-emitting radiation but non-scattering medium. The dimensionless governing equations are solved by an efficient, more accurate, unconditionally stable and fast converging implicit scheme. The effects of velocity and temperature for different parameters such as the thermal radiation, magnetic field, Schmidt number, thermal Grashof number and mass Grashof number are studied. It is observed that the velocity decreases in the presence of thermal radiation or a magnetic field.
Keywords: radiation; magnetic field; vertical plate; finite-difference